FASHION SHOWS IN ARCHAEOLOGICAL HERITAGE SITES - Allegranti, Ivan (Design/Arts/Culture, 2020)
This article has the aim to investigate the relationship between fashion and archaeological heritage sites. This paper start from the analysis of the International Laws regulating the protection both of cultural heritage as well as archaeological heritage such as the UNESCO World Heritage Convention of 1972 or article 167 of the Treaty on the Functioning of Europe. After, it will be devoted to outline the international recommendations on the preservation of cultural heritage. Soon after, the paragraph 5 traces the relationship between archaeological heritage sites and fashion shows made by the most important fashion brands in the world. For instance, paragraph 5 of the paper analyzes a concrete case of a show, the show of Greek designer Mary Katrantzou who showed her collection at the Temple of Poseidon on top the Cliff of Cape Sounion. Thanks to this, it will be analyzed Greek’s law on the protection of antique and cultural heritage. The main achievement of this research, achieved trough the reading and in-depth analysis of international laws, international conventions and the Greek Law 3028/2002 “On the Protection of Antiquities and Cultural Heritage in General”, is the outlining of the discipline concerning private events in archaeological heritage spaces in Greece.